Classroom presentation on water with children holding shovels - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a classroom with children seated at the right, wearing tall boots and hats. Some of the children are holding shovels. On the wall there is a panel of drawings that depict an aquaduct, and hand-drawn maps of California. On the table in the center is a model of a fountain surrounded by landscaping.